2016
DOI: 10.1021/acs.jpcb.6b08091
|View full text |Cite
|
Sign up to set email alerts
|

Proton Probability Distribution in the O···H···O Low-Barrier Hydrogen Bond: A Combined Solid-State NMR and Quantum Chemical Computational Study of Dibenzoylmethane and Curcumin

Abstract: We report a combined solid-state (H, H,C, O) NMR and plane-wave density functional theory (DFT) computational study of the O···H···O low-barrier hydrogen bonds (LBHBs) in two 1,3-diketone compounds: dibenzoylmethane (1) and curcumin (2). In the solid state, both 1 and 2 exist in the cis-keto-enol tautomeric form, each exhibiting an intramolecular LBHB with a short O···O distance (2.435 Å in 1 and 2.455 Å in 2). Whereas numerous experimental (structural and spectroscopic) and computational studies have been rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 68 publications
5
60
0
Order By: Relevance
“…[10,[15][16][17][18][19][20][21][22][23][24][25][26][27][28] The perplexity caused by the relative stability of the asymmetric and symmetric DBM's protic tautomers is due to the inability of experimental scattering and spectroscopic techniques to resolve ultrafast proton motion in the hydrogen bond, but also possibly due to various experimental conditions and aggregate states in which DBM was studied. [10,[15][16][17][18][19][20][21][22][23][24][25][26][27][28] The perplexity caused by the relative stability of the asymmetric and symmetric DBM's protic tautomers is due to the inability of experimental scattering and spectroscopic techniques to resolve ultrafast proton motion in the hydrogen bond, but also possibly due to various experimental conditions and aggregate states in which DBM was studied.…”
Section: The Effects Of Hydrogen Bonding and Homogeneous Electric Fiementioning
confidence: 99%
“…[10,[15][16][17][18][19][20][21][22][23][24][25][26][27][28] The perplexity caused by the relative stability of the asymmetric and symmetric DBM's protic tautomers is due to the inability of experimental scattering and spectroscopic techniques to resolve ultrafast proton motion in the hydrogen bond, but also possibly due to various experimental conditions and aggregate states in which DBM was studied. [10,[15][16][17][18][19][20][21][22][23][24][25][26][27][28] The perplexity caused by the relative stability of the asymmetric and symmetric DBM's protic tautomers is due to the inability of experimental scattering and spectroscopic techniques to resolve ultrafast proton motion in the hydrogen bond, but also possibly due to various experimental conditions and aggregate states in which DBM was studied.…”
Section: The Effects Of Hydrogen Bonding and Homogeneous Electric Fiementioning
confidence: 99%
“…[9,16] Figure 3b shows the results of the planewave DFT MD simulations for NA as a2Dproton probability distribution in the q 1 -q 2 space where q 1 = (r OH Àr HN )/2 and q 2 = (r OH + r HN )a re the natural hydrogen bond coordinates commonly used in the valence bond order analysis. [9,16] Figure 3b shows the results of the planewave DFT MD simulations for NA as a2Dproton probability distribution in the q 1 -q 2 space where q 1 = (r OH Àr HN )/2 and q 2 = (r OH + r HN )a re the natural hydrogen bond coordinates commonly used in the valence bond order analysis.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[9,16] Figure 3b shows the results of the planewave DFT MD simulations for NA as a2Dproton probability distribution in the q 1 -q 2 space where q 1 = (r OH Àr HN )/2 and q 2 = (r OH + r HN )a re the natural hydrogen bond coordinates commonly used in the valence bond order analysis. [9,16] Fore xample,D urlak and Latajka [16c] reported very similar results for benzoylacetone.T hey further showed that the two "peaks" seen in classic ab initio MD simulations merge into one in path-integral MD simulations which take full account of the nuclear quantum effects.T hus,o ur MD data support the conclusion about the LBHB formation in NA.InFigure 3b,the theoretical curve from the valence bond order model is also shown for comparison. [9,16] Fore xample,D urlak and Latajka [16c] reported very similar results for benzoylacetone.T hey further showed that the two "peaks" seen in classic ab initio MD simulations merge into one in path-integral MD simulations which take full account of the nuclear quantum effects.T hus,o ur MD data support the conclusion about the LBHB formation in NA.InFigure 3b,the theoretical curve from the valence bond order model is also shown for comparison.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…Their bond energies can be as great as ~37 kcal/mol, and their donor–acceptor distances can be as short as ~2.2 å . Typical O…O distances of LBHBs are ~2.4 å . LBHBs are found in many organic molecules as well as in some enzymes .…”
Section: Introductionmentioning
confidence: 99%